CORRELATION BETWEEN STUDENTS’ INTEREST IN WATCHING MUSIC VIDEO AND THEIR LISTENING ABILITY - Nida Rahmatinnisa; Titin Rohaeti (PROJECT (Professional Journal of English Education), 2018)
The purpose of this research was to find out whether or not students’ interest in watching music video and their listening ability have a significant correlation. The method used in this research was a quantitative research method. The population of the research is the first grade students of SMK Al-Hasyimiyah which is located on Jl. Hanjawar Pacet Cianjur. This research was conducted in March 2018 in the 2017/2018 academic year. And the researchers took TKJ class with consist 33 students for the sample out of the population. The data were collected by questionnaire and test, and then the data were analyzed using the correlation analysis. The result of the research showed that students interest in watching music video gave a positive contribution to students listening ability. It can be seen from the result of corrrelation coefficient between the two variables in this resesarch is 0.583. And the correlation between two variable was significant because sig (2-tailed or 0.000) was lower than 0.05. In other word that there was significant correlation between students interest in watching music video and their listening ability.